SPIRITUALITAS BUDDHIS DALAM PENGAMBILAN KEPUTUSAN UNTUK MENENTUKAN HARGA JUAL - Dini Sulistiyani; Warsito Kawedar (Diponegoro Journal of Accounting, 2023)
The research entitled "Buddhist Spirituality in Making Decisions to Determine Selling Prices" aims to determine the role of Buddhist spirituality in decision making by business actors to determine the selling price of their products. This study uses a descriptive qualitative approach to provide an overview or description of the role of Buddhist spirituality in business actors. Data was collected through in-depth interviews with four business actors who are Buddhist or study Buddhism and four buyers as supporting informants to complete the research data. The data obtained was then analyzed and reduced so that the data needed to be presented was obtained. The findings from the practice of determining selling prices are presented through a Buddhist perspective. The results of the study show that in determining the selling price by Buddhist business actors there are non-material values in it, namely the value of morality (sila) and the value of love (metta). In addition, there are other values that play a role in business activities by business actors. The business activities carried out by the informants are not solely aimed at seeking profit, but also to establish good and loving relationships between human beings.